Compost substrate conditions and bacterial community structure in small-scale food waste composting systems for household implementation / Muhammad Azri Amran - Muhammad Azri , Amran (2023)
Waste generated in rural areas are poorly managed and treated, mainly due to the lack of access and coverage by the authorities resulting in potential social, health and economic problems if left untreated. One proposed approach is through small-scale composting for household which was intended to manage waste in a sustainable manner to develop compost product that is suitable for application or income generation under the circular economy concept. This project assessed the composting performance, microbial dynamics and suitability in application of compost generated through four different treatments which were; A - Aeration and microbial additives, B - Microbial additives only, C - Aeration only, and D - No treatment/ control. Small scale composting was performed on a mixture of food waste and bulking agent (1:1 ratio) in triplicates for a duration of 14 weeks. By the final week 14, all the compost from the four different treatment groups had reached maturity phase, which was established by the biochemical indicator such as temperature (26-30°C), pH level (>8), and C/N ratio (10-14). The Firmicutes, Proteobacteria, and Actinobacteria were dominating bacterial phyla and its abundance throughout composting were documented as it supported the maturity of compost. Treatment A generated compost within recommended maturity parameters and promoted growth of crop in a germination experiment. The small-scale food waste composting system is feasible and is a practical approach for waste management in any household.